Quality of life among pediatric residents in Riyadh - Almhizai, Rheem A.; Alnazha, Meshari N.; Alharbi, Rola F.; AlRumaih, Norah A.; Alkharashi, Abdullah A.; Albadi, Abdulmalik K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Until now, no locally based study has evaluated quality of life among pediatric residents, especially pediatric residents in Saudi Arabia, Riyadh. The objective of this study was to evaluate quality of life (QoL) of the pediatric residents and report the factors affecting their quality of life. Methods: A cross-sectional study, a self-administered questionnaire depending study that was distributed electronically to pediatrics resident to assess the quality of life in Riyadh, Saudi Arabia. The study depended on self-reported questionnaire in which the questions were gathered specifically, from work-related quality of life (WRQoL) scale. To collect data, the self- administered questionnaire was sent through social media (twitter, WhatsApp). Results: In this study, we were able to collect data from 260 residents where 54.2% of them were females. In general, we found that 51.9% of the participants showed good level of QoL while 47.7% showed moderate level of quality of life and only 0.4% showed low levels of QoL. The percentage of residents who showed good quality of life among the six categories; CAW, JCS, HWI, SAW, GWB and WCS were 53.8%, 49.2%, 45.0%, 48.6%, 38.1% and 56.9% respectively. We did not find any significant factors that had impact on quality of working life among the residents. Conclusions: We found that 48.2% of the pediatric residents working in Al Riyadh region, Saudi Arabia showed moderate to low level of work-related QoL. Further studies are needed to determine the causes and improve the work-related quality of life among pediatric residents.